2021
DOI: 10.4103/jfmpc.jfmpc_2182_20
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary blood donation among female health care university students in Saudi Arabia, knowledge and status

Abstract: Context: Blood donation is an essential lifesaving procedure. There is a continuous effort to supply the high demand in hospitals. Aims: To assess the current status, knowledge, and attitudes of female health care students in King Saud Bin Abdulaziz University for Health Sciences (KSAU-HS) regarding blood donation. Settings and Design: A cross-sectional study was done with students in the female campus of KSAU-HS in Riyadh. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…of the participants in this study, this is in keeping with the study among female students in Saudi Arabia [18]. Religious organizations usually make these appeals when one of their members is in need of blood with a good response, especially from men.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…of the participants in this study, this is in keeping with the study among female students in Saudi Arabia [18]. Religious organizations usually make these appeals when one of their members is in need of blood with a good response, especially from men.…”
Section: Discussionsupporting
confidence: 69%
“…However, these studies were predominantly among blood donors who are dominated by men. Some studies conducted among female participants outside Nigeria have identified altruism, the feeling of responsibility, positive effect on health and moral or religious obligation as motivators [17,18], while fear of anaemia or weakness and dizziness were some barriers identified [17]. Very little is known about female blood donors and the inherent factors that could promote or deter them from blood donation in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Fear of seeing own blood, fear of the procedure itself and negative experiences from previous, first-time blood donation or lack of appropriate "incentives", eg, financial, may be an additional barrier for young people. [17][18][19][20][21][22][23][24][25] Interestingly, women, who are more altruistic than men and more motivated to donate blood, 19 accounted for only 1/4-1/3 of all donors in our analysis (Table 3). On the other hand, a similar proportion of female blood donors was also observed in other countries.…”
Section: Dovepressmentioning
confidence: 92%
“…Blood donation has become a vital part of any health care institution since it cannot be generated artificially and can only be received from human resources [1,2]. In surgical operations, trauma, Hematological illnesses, and pregnancy-related issues, the blood given might be utilized [3]. There's no way to keep blood indefinitely, and there's no way to make it synthetically.…”
Section: Introductionmentioning
confidence: 99%
“…There was no longer any need for Saudi Arabian hospitals to import foreign-blooded donors after 1981. This growing need for blood cannot be met with the current supply of donors [3].…”
Section: Introductionmentioning
confidence: 99%